Toxic effects of nanopolystyrene and cadmium on the intestinal tract of the Chinese mitten crab (Eriocheir sinensis) - Shunli Che; Mengting Huang; Huiying Ma; Zhicheng Wan; Jianbin Feng; Shuquan Ding; Xilei Li (Ecotoxicology and Environmental Safety, 2024)
Nanopolystyrene (NP) and cadmium (Cd) are ubiquitous contaminants in aquatic systems. The present study aimed to investigate the toxic effects of exposure to ambient concentrations of NP and/or Cd on the intestinal tract of the Chinese mitten crab (Eriocheir sinensis). Exposure to NP and/or Cd induced oxidative stress, as evidenced by a significant increase in lipid peroxide content (LPO), total antioxidant capacity (T-AOC), and peroxidase activity (POD), and significant decreases in superoxide dismutase (SOD) and glutathione peroxidase (GSH-PX) activities in E. sinensis. In addition, exposure to NP and/or Cd imbalanced the homeostasis of the intestinal microbiota, as demonstrated by the significantly increased abundance of Spiroplasma. Transcriptomic and metabolomic analyses were performed to investigate the mechanisms underlying intestinal toxicity. Our results showed that ferroptosis, ABC transporters, phosphotransferase system, apoptosis, and leukocyte transendothelial migration were disturbed after exposure to NP and/or Cd. In particular, Cd exposure affected mucin type O-glycan biosynthesis, purine metabolism, and neuroactive ligand-receptor interaction. Intriguingly, co-exposure to NP and Cd might mitigate intestinal toxicity by decreasing oxidative stress and affecting these pathways. Taken together, our study clearly demonstrates that exposure to NP and/or Cd at environmentally relevant concentrations causes intestinal toxicity in E. sinensis.